2013
DOI: 10.1371/journal.pone.0067720
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Forest Diversity and Biomass on a Tropical Volcano, Mt. Rinjani, Lombok, Indonesia

Abstract: Tropical volcanoes are an important but understudied ecosystem, and the relationships between plant species diversity and compositional change and elevation may differ from mountains created by uplift, because of their younger and more homogeneous soils. We sampled vegetation over an altitudinal gradient on Mt. Rinjani, Lombok, Indonesia. We modeled alpha- (plot) and beta- (among plot) diversity (Fisher's alpha), compositional change, and biomass against elevation and selected covariates. We also examined comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 66 publications
(69 reference statements)
3
24
0
2
Order By: Relevance
“…Temperature stress at high altitudes could result in phylogenetic clustering, as reported for other taxa like birds, bees, butterflies, microbes (Qian et al, 2014 and references therein), and plants (e.g., Dossa et al, 2013). However, we found deep phylogenetic overdispersion in higher elevation forests.…”
Section: Distinct Causes Of Phylogenetic Overdispersionsupporting
confidence: 76%
“…Temperature stress at high altitudes could result in phylogenetic clustering, as reported for other taxa like birds, bees, butterflies, microbes (Qian et al, 2014 and references therein), and plants (e.g., Dossa et al, 2013). However, we found deep phylogenetic overdispersion in higher elevation forests.…”
Section: Distinct Causes Of Phylogenetic Overdispersionsupporting
confidence: 76%
“…Compared with TMF outside Africa, our AGB estimates (which range from 117 to 612 Mg ha -1 , mean of all plots studied 276 Mg ha -1 ) seem high, particularly in Mt Nyiro. For example, AGB ranged between and 200 Mg ha -1 (1500-2500m) in Andean TMF (Girardin et al, 2014), between 100 and Mg ha -1 (1000 and 2200m) at Mt Rinjani in Indonesia (Dossa et al, 2013), while it was estimated at Mg ha -1 and 271 Mg ha -1 for submontane and montane Atlantic forest in Brazil (Alves et al, 2010). Interestingly, it has been reported that Asian and Neotropical TMFs have similar mean AGB (257 and 247 Mg ha −1 , n = 31 and 56, respectively) while that of African TMF is higher (527 Mg ha −1 n = 7) (Spracklen and Righelato, 2014).…”
Section: The Variable Agb Per Forest Typementioning
confidence: 99%
“…Generally, there is a decline in tree species richness with increasing altitude (e.g. Dossa et al, 2013;Sassen and Sheil, 2013;Girardin et al, 2014), because of a greater role of environmental filtering at higher elevations (e.g. cooler temperatures, fog, reduced light incidence and higher relative humidity).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers have found that forest diversity is positively linked with aboveground biomass [45][46][47][48][49]. However, the quantitative relationship between AGB and structure -species diversity is poorly understood.…”
Section: Novel Contributionmentioning
confidence: 99%